FAKTOR-FAKTOR YANG MEMPENGARUHI YIELD TO MATURITY OBLIGASI - ARIINA ADILA; MUHAMMAD RIDWAN (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Bond yields represent income received by bondholders and one of the benchmarks used by investors to monitor the development of bond market. This study aims to test and obtain empirical evidence regarding the effect of the Interest Rate, Debt to Equity Ratio and firm size on the interest yield (Yield To Maturity) of corporate bonds. This study uses a sample of banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022 wich have Bonds on the Indonesia Stock Exchange (IDX) in 2018-2022 . This study was conducted on the Indonesia Stock Exchange (IDX) with secondary data obtained from the IDX, the IDX Bond Book, and the financial reports of each sample company. The sample determination method used in this study is purposive sampling using Eviews 12 for data analysis. This type of research is quantitative with 12 companies used as research samples with observations for 5 years, so the total research sample is 60 samples. The data analysis technique used is multiple linear regression. The results of this study indicate that partially the interest rate has a significant effect on Yield To Maturity, partially the Debt to Equity Ratio has no significant effect on Yield To Maturity, partially firm size has a significant effect on Yield To Maturity. Simultaneously, Interest Rates, Debt to Equity Ratio and firm size have an impact on Yield To Maturity. These results support the findings of several previous studies which also strengthen the position of interest rates and firm size as determinants of yield.